A Regional Model of Topside Ionospheric Effective Scale Heights Derived From Ionosonde and GNSS TEC - Chunhua Jiang; Zhichao Liu; Cong Zhao; Tongxin Liu; Guobin Yang; Hua Shen; Wengeng Huang (Space Weather)
Abstract Ionospheric scale height is critical for the structure of electron density profile in the ionosphere. However, mostly, the effective scale heights (fitted with mathematical functions) instead of topside ionospheric scale heights were used to reconstruct the topside profile. In this study, a new method was proposed to estimate topside ionospheric effective scale heights from ionosonde and Global Navigation Satellite System (GNSS) vertical total electron content (TEC). First, the bottomside electron density profile can be estimated from ionograms. Then, combined the parameters of the F2 layer and effective scale heights, topside electron density profile can be estimated by Epstein Layer. Furthermore, ionosonde TEC can be compared with GNSS vertical TEC by adjusting effective scale heights to obtain best‐fit ionosonde TEC and effective scale heights. In this study, ionosonde and GNSS TEC data recorded at Zhangye station (39.40°N, 100.13°E) were used to test the performance. Results show that diurnal and seasonal characteristics of effective scale heights are consistent with previous studies. Furthermore, the Empirical Orthogonal Function technique was used to build a regional and empirical model of effective scale heights. Results show that the accuracy (between ±2.5 TECU) of ionosonde TEC are about 91.26% by comparing with GNSS TEC. Considered that the traditional methods mostly underestimated TEC, it indicates that the accuracy of ionosonde TEC can be improved significantly by the new model of effective scale heights. Furthermore, results show that the topside electron densities estimated by the proposed method are comparable with in situ observations measured by Swarm B.